Pectin Esterase Production from Apple Pomace in Solid-State and Submerged Fermentations - Mukesh Parmar; Neerja S. Rana; Vinod Kumar Joshi (Food Technology and Biotechnology, 2006)
Comparison of the production of pectin methylesterase (PME) by Aspergillus niger from apple pomace in solid-state (SSF) and submerged fermentation (SmF) was made for higher PME production. pH value of 4.0, incubation temperature of 25 °C and incubation period of 96 h were found optimum in both SSF and SmF, while optimum dilution levels were 1:3 and 1:6, respectively. Ammonium sulphate in SSF and diammonium hydrogen phosphate in SmF as nitrogen sources at the rate of 0.2 % gave the highest yield of PME. Sodium chloride at the rate of 0.5 % in SSF and manganese sulphate at the rate of 2 % in SmF as additives gave the highest yield of PME. Overall, the SSF gave 2.3 times higher PME activity than SmF, using optimized parameters of fermentation.